Theology and Ethics in Values-Based Journalism Communicating Islamic Perspectives - Ahmad Salman Farid; Rizka Ar Rahmah; Irmasani Daulay; Desiana (Pharos Journal of Theology, 2024)
This research explores the intersection of theology and ethics within the realm of values-based journalism, with a specific focus on the communication of Islamic perspectives. In the contemporary media landscape, where journalism plays a crucial role in shaping public discourse, it becomes imperative to analyze how Islamic values are communicated through the lens of ethical journalism. The study aims to investigate the application of Islamic theology and ethical principles in values-based journalism, emphasizing the role of media in reflecting and shaping societal norms. By employing a qualitative research approach, content analysis will be conducted on a sample of news articles, opinion pieces, and other journalistic content with an Islamic focus. The analysis will delve into how these pieces adhere to or deviate from established theological principles and ethical guidelines. Furthermore, the research seeks to identify challenges faced by journalists and media organizations when attempting to integrate Islamic values into their narratives. It also explores potential strategies and best practices for overcoming these challenges, fostering a more nuanced and ethical communication of Islamic perspectives. The findings of this study aim to contribute to the ongoing discourse on the role of theology and ethics in journalism, providing insights into how media professionals can effectively communicate Islamic values while upholding ethical standards. Ultimately, the research aspires to encourage a more informed and respectful portrayal of Islamic perspectives in the media, promoting dialogue and understanding in an increasingly diverse and interconnected global society.